2010
DOI: 10.1021/jf102621c
|View full text |Cite
|
Sign up to set email alerts
|

trans-Fatty Acid Isomers in Two Sesame (Sesamum indicum L.) Seed Byproducts under Processing

Abstract: The present study has been inspired by the growing need for rigorously controlling the nutritional quality and safety of food products. The impact of application in the food industry on fatty acids composition, trans-fatty acids (TFAs), and conjugated linoleic acid (CLA) profiles were investigated in a highly consumed candy byproduct of sesame seed (chamia) in comparison to fresh sesame seed oil (SSO) and heated SSO under simulated frying experiments. The effect of treatment on SSO was studied by determining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…, 2003). As previously observed by Dhibi et al. (2010), the high‐temperature treatment induces positional isomerisation and increases the total amount of CLA in heated sesame seed oil.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…, 2003). As previously observed by Dhibi et al. (2010), the high‐temperature treatment induces positional isomerisation and increases the total amount of CLA in heated sesame seed oil.…”
Section: Resultssupporting
confidence: 73%
“…CLA are a specific group of positional and geometric isomers derived from linoleic acid (LA) that formed during heating (Juane´da et al, 2003). As previously observed by Dhibi et al (2010), the high-temperature treatment induces positional isomerisation and increases the total amount of CLA in heated sesame seed oil. A close positive correlation was found between the total trans isomers and the heating period at frying temperature (R 2 = )0.975).…”
Section: Fatty Acid Compositionmentioning
confidence: 84%
“…FAMEs were identified by comparing their relative and absolute retention times to those of authentic cis-fatty acid (CFA) and TFA standards. The FA composition was reported as a relative percentage of the total peak area using a HP Chemstation integrator [ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other studies have reported that Sesamun indicum has potential antioxidant, anti-hypertensive, and anti-hyperlipidemic effects [18]. Recent phytochemical studies found that Sesamun indicum contained several lignans, including sesamol, sesamin, sesamolin, and sesaminol [20].…”
Section: Discussionmentioning
confidence: 99%
“…(Sesame) is an important oil crop [17]. Sesame seed oil contains high levels of unsaturated fatty acids, including linoleic acid and linolenic acid [18]. Sesame seed oil also contains beneficial vitamins and minerals that regulate physiological functions [19].…”
Section: Introductionmentioning
confidence: 99%